Contribution of speed to running anaerobic sprint test (RAST) performance in professional Greek soccer players - Volianitis, S.; Bakas, G.; Manouras, N.; Flouris, A. D.; Famisis, K. (Inquiries in Sport & Physical Education, 2020)
The running anaerobic sprint test (RAST) evaluates repeated sprint ability and its relation to maximal speed. However, the association between RAST and other speed parameters has attracted little scientific attention. The purpose of this study was to establish the relationship amongst RAST performance measures to first step quickness (5 m), acceleration (10 m), maximal speed (30 m), 5-10 m and 20-30 m splits in professional soccer players. Nineteen Greek professional soccer players were tested for RAST performance, first step quickness, acceleration and maximal speed during the preseason. Mean time (RASTmean), percent decrement (%dec) and fatigue index (FI) were also calculated. RASTmean had a likely moderate relationship to 10 m (r=0.33; 90%CL, -0.07 to 0.67), most likely large relationship to 5-10 m (r=0.60; 90%CL, 0.27 to 0.80), likely moderate relationship to 20 m (r=0.32; 90%CL, -0.08 to 0.63), very likely large relationship to 30 m (r=0.60; 90%CL, 0.26 to 0.80) and a most likely large relationship to 20-30 m (r=0.70; 90%CL, 0.43 to 0.86). %decbest were likely moderately slower in 5 m (r=0.88; 90%CL, 0.12 to 1.64), 10 m (r=0.93; 90%CL, 0.19 to 1.68), 20 m (r=0.68; 90%CL, -0.12 to 1.48) and 30 m (r=0.70; 90%, 0.09 to 1.49) compared to %decworst. Similarly, FIbest were likely moderately slower in 5 m (r=0.66; 90%CL, -0.14 to 1.46), 10 m (r=0.95; 90%CL, 0.22 to 1.69), 5-10 m (r=0.76; 90%CL, -0.03 to 1.54), 20 m (r=0.78; 90%CL, -0.01 to 1.57), 30 m (r=0.92; 90%CL, 0.17 to 1.67) and 20-30 m (r=0.61; 90%CL, -0.20 to 1.41) compared to FIworst. In conclusion, RASTmean had the strongest association with maximal speed. On the other hand, %dec and FI indices are negatively associated to all speed parameters and slower speed performance.